The Use of Ice Breakers in Online English Grammar Classes - Asfi Aniuranti (Faculty of Language and Literature, University of Surakarta, 2021)
In the English language teaching process, every teaching phase is paramount for the achievement of its goals. At the beginning of the classes, the teachers might bring an ice breaker. Based on the previous studies, ice breaker is considered a crucial component in EFL classes. Considering the prominence of ice breakers, the researcher regards the importance of a literature study about ice breakers, especially in grammar class. English grammar is frequently considered a complicated element. Besides, nowadays, the learning process has to be conducted online. This study is mainly aimed to explain the concept of ice breakers, English grammar, and online learning, and the examples of ice breaking possibly used in online grammar classes. The method employed was the literary study conducted through several stages called collecting, reducing and presenting the data and concluding the results. This study suggests several relevant theories to the usage of ice breakers in online grammar classes. Moreover, this study proposes some ice breakers for teaching grammar. The ice breakers are jumbled sentences, correcting mistakes, English songs, storytelling activities, and English humour.